2021
DOI: 10.3389/fimmu.2021.708186
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages: The Good, the Bad, and the Gluttony

Abstract: Macrophages are dynamic cells that play critical roles in the induction and resolution of sterile inflammation. In this review, we will compile and interpret recent findings on the plasticity of macrophages and how these cells contribute to the development of non-infectious inflammatory diseases, with a particular focus on allergic and autoimmune disorders. The critical roles of macrophages in the resolution of inflammation will then be examined, emphasizing the ability of macrophages to clear apoptotic immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(160 citation statements)
references
References 279 publications
(320 reference statements)
4
154
0
2
Order By: Relevance
“…However, Th1 cells have a higher degree of differentiation, which indicates that VLPs are more inclined to cellular immune responses. Furthermore, consistent with our results, previous studies have revealed that M1-type macrophages have the function of mediating Th1 immune responses (19). We also tested the culture supernatants for the levels of inflammatory cytokines and found that IL-18, IL-6 and TNF-a were all increased in cocultures exposed to VLPs (Figures 6C-E), indicating that Mø antigen presentation may be activated through inflammatory pathways.…”
Section: Discussionsupporting
confidence: 91%
“…However, Th1 cells have a higher degree of differentiation, which indicates that VLPs are more inclined to cellular immune responses. Furthermore, consistent with our results, previous studies have revealed that M1-type macrophages have the function of mediating Th1 immune responses (19). We also tested the culture supernatants for the levels of inflammatory cytokines and found that IL-18, IL-6 and TNF-a were all increased in cocultures exposed to VLPs (Figures 6C-E), indicating that Mø antigen presentation may be activated through inflammatory pathways.…”
Section: Discussionsupporting
confidence: 91%
“…However, Th1 cells have a higher degree of differentiation, which indicates that VLPs are more inclined to cellular immune responses. Furthermore, consistent with our results, previous studies have revealed that macrophages the function of Th1 immune responses (19). We also tested the culture supernatants for the levels of inflammatory cytokines and found that IL-18, IL-6 and TNF-a were all increased in cocultures exposed to VLPs (Figures 6C-E), indicating that Mø antigen presentation may be activated through inflammatory pathways.…”
Section: Discussionsupporting
confidence: 90%
“…M1 macrophages express high levels of interleukin-12 (IL-12) and IL-23, inducing inflammatory responses and promoting immunity responses to suppress tumor growth. Conversely, M2 macrophages express high levels of IL-10 and scavenger receptor, can promote tumor angiogenesis and immunosuppression, facilitating tumor angiogenesis and immunologic suppression [ 75 ]. Liao et al [ 76 ] designed methylcellulose (MC) hydrogel incorporating LOX (MC-LOX) for repolarization of M2 to M1 macrophages by consuming lactic acid in the TME.…”
Section: Oxidase-mediated Starvation Therapy and Oxidative Therapymentioning
confidence: 99%